[Speech Being Given at Bonfire] (1961)
Week of Welcome (WOW), Fall 1961. Students gathered around bonfire in Cambria, at either Camp Pine Crest or Camp Ocean Pines. Printed in 1962 El Rodeo Yearbook, pg. 26.